Mode of Action of a Purified Antitumor Protein from the Proteinaceous Crystal of Bacillus thuringiensis subsp. thuringiensis on Yoshida Ascites Sarcoma Cells - Prasad, S. S. S. V. (1976)
A purified antitumor protein from the proteinaceous crystal of Bacillus thuringiensis subsp. thuringiensis inhibits the growth of Yoshida ascites sarcoma both in vivo and in vitro. Exogenous respiration of the tumor cells was unaffected by the protein at a concentration as high as 500 μg/ml. The antitumor protein inhibits the uptake and incorporation of labeled precursors into macromolecules. However, the ratio of incorporation over uptake is not affected by the protein. Further, the protein brings about the leakage of 260-nm-absorbing material, proteins, and (32)P-labeled cellular constituents from the Yoshida ascites sarcoma cells. The results show that the action of the antitumor protein appears to alter the cellular permeability of the tumor cells.